Inclusion properties of certain subclasses of analytic functions - Darus, Maslina; Faisal, Imran (SABER-ULA, 2011)
The purpose of the present paper is to introduce several new classes of analytic functions and investigate various inclusion properties of these classes. Some interesting applications of integral operators are also considered.
Keywords: Departamento de Matemática; Facultad de Ciencias; Analytic functions; Differential operators; Integral-preserving properties; Matemáticas; Revistas